Public policies in the management of sexual and gender diversity: An intersectional analysis - Carmen Romero Bachiller; Universidad Complutense de Madrid; Marisela Montenegro Martínez; Universidad Autónoma de Barcelona (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2018)
Institutional management of diversity has focussed on producing policies and interventions towards the inclusion and/or normalization of collectives defined as minorities. The concept of intersectionality has contributed to complexify processes of sectorialization derived from this perspective, introducing the idea of co-functioning of different sources of oppression. Departing from the intersectional analysis of two laws, one from Generalitat of Catalonia and the other from Madrid Autonomous Community, aiming to guarantee rights for gender and sexualy diverse people and against LGTBIphobia, we describe the effects of homogenization, essentialization and normalization as well as the dynamics of hierarchization and exclusion that the processes of normative categorization generate. We propose understanding the concept of intersectionality from a situational and relational perspective, implying that practices of domination emerge in concrete contexts where certain differences appear as relevant in each particular definition of given relations. Those processes, framed in historically constituted normative configurations, occur as concrete condensations of inequalities and hierarchies.